2016
DOI: 10.1590/1807-1929/agriambi.v20n9p817-822
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation management strategy for Prata-type banana

Abstract: A B S T R A C TThis study aimed to analyze different irrigation strategies in two cultivars of the banana crop. The study was conducted in four production cycles of 'Prata-Anã' and 'BRS Platina' bananas. The applied irrigation depths (ID) were obtained by the model ID = K x LA x ETo, where K is an empirical transpiration constant of 0.20; 0.35; 0.50 and 0.65 for the strategies 1, 2, 3 and 4, respectively; LA is the leaf area of mother and daughter plants of 'Prata-Anã' and ETo is the reference evapotranspirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
1
3
2
Order By: Relevance
“…Similar findings on reducing irrigation depths were obtained by Santos et al (2016), who observed, in Prata-Anã and BRS Platina, a decrease in the water-use efficiency with increasing irrigation depths, since yield is not consistent with increasing e-ISSN 1983-4063 -www.agro.ufg.br/pat -Pesq. Agropec.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Similar findings on reducing irrigation depths were obtained by Santos et al (2016), who observed, in Prata-Anã and BRS Platina, a decrease in the water-use efficiency with increasing irrigation depths, since yield is not consistent with increasing e-ISSN 1983-4063 -www.agro.ufg.br/pat -Pesq. Agropec.…”
Section: Resultssupporting
confidence: 81%
“…Conversely, Donato et al (2015b) reported that well-managed banana plantations under better conditions of climate, such as maximum temperatures below 34 ºC, less windrelated damage and higher relative humidity, i.e., favoring a higher carboxylation and instantaneous water-use efficiency (Donato et al 2015a, Arantes et al 2016, Ramos et al 2018, may yield more than 40 t ha -1 cycle -1 (high yield > 32 t ha -1 cycle -1 ), particularly from the second production cycle on. The lack of irrigation depth effect on the yield of the first production cycle was also observed by Santos et al (2016), who, by studying Prata-Anã and BRS Platina, did not verify differences in yield between the two cultivars or lack of effects for lowering the irrigation depth, although the yield recorded herein (20.25 t ha -1 ) was higher than that found by Santos et al (2016) (9.59 t ha -1 ). It is worth noting that, in the experiment carried out by Santos et al (2016), the planting density was 1,333 plants ha -1 and the plants were watered by drip irrigation.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…Plant density averaged 1332 plants ha −1 (4.0 m × 2.0 m double row, 2.5 m between plants). Plants were sprinkler-irrigated at a crop evapotranspiration ( ET c ) rate proportional to potential evapotranspiration ET 0 ( ET c = K C ET 0 , where K C varied during the season) 6 , 57 . To sustain high yield and quality, the banana clump was restricted to a few fruiting plants by yearly pruning.…”
Section: Methodsmentioning
confidence: 99%
“…This genotype produces fruits of greater length and heavier when produced in the absence of water deficit (Castricini et al, 2012) which explains the greater length of dried banana in the highest applied irrigation level On the other hand, irrigation effect was not observed in the length (p>0.05) for dried bananas of Prata-Anã and FHIA-18 genotypes, whose values were 101.56 and 109.09 mm, respectively. Banana 'Prata-anã' proved to be less sensitive to moderate hydric stress than 'BRS Platina' banana (Santos et al, 2016). Unlike Braga Filho et al (2011) who found in a study with the variety FHIA, influence of irrigation in the fruit length.…”
Section: Effect Of Water Deficit On the Physical Parameters Of Dried mentioning
confidence: 72%